2018
DOI: 10.3390/brainsci8120226
|View full text |Cite
|
Sign up to set email alerts
|

NRSF and Its Epigenetic Effectors: New Treatments for Neurological Disease

Abstract: The Neuron Restrictive Silencer Factor (NRSF) is the well-known master transcriptional repressor of the neuronal phenotype. Research to date has shown that it is an important player in the growth and development of the nervous system. Its role in the maturation of neural precursor cells to adult neurons has been well characterized in stem cell models. While much has been characterized from a developmental perspective, research is revealing that NRSF plays a role in various neurological diseases, ranging from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Further studies mixing various musculoskeletal conditions could longitudinally assess both painDETECT (and/or DN4) scores and daily pain duration (eg, using a diary to assess it prospectively), early after the onset of a new pain episode to reproduce, or not, these findings. Similar observations would suggest that high painDETECT scores do not require lasting anatomical lesions in peripheral nerves or the central nervous system but may rather result from early epigenetic changes 37,40 and/or genetically encoded traits, leading to more rapid sensitization of neurons or glial cells. Genetic traits indeed appeared to be nearly as important as environmental or traumatic influences for high painDETECT scores in a recent large epidemiological study of 4324 people and 1357 twins, which concluded that, as for chronic widespread pain, high painDETECT scores were best explained by a combination of similar heritable traits, accounting for 37% (95% CI: 23%–50%) of the variance, and unique environmental factors, accounting for 63% (95% CI: 49%–79%).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Further studies mixing various musculoskeletal conditions could longitudinally assess both painDETECT (and/or DN4) scores and daily pain duration (eg, using a diary to assess it prospectively), early after the onset of a new pain episode to reproduce, or not, these findings. Similar observations would suggest that high painDETECT scores do not require lasting anatomical lesions in peripheral nerves or the central nervous system but may rather result from early epigenetic changes 37,40 and/or genetically encoded traits, leading to more rapid sensitization of neurons or glial cells. Genetic traits indeed appeared to be nearly as important as environmental or traumatic influences for high painDETECT scores in a recent large epidemiological study of 4324 people and 1357 twins, which concluded that, as for chronic widespread pain, high painDETECT scores were best explained by a combination of similar heritable traits, accounting for 37% (95% CI: 23%–50%) of the variance, and unique environmental factors, accounting for 63% (95% CI: 49%–79%).…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, functional and very early changes in peripheral nerves or the central nervous system (ie, more neuroplastic than neuropathic, such as epigenetic changes in neurons and/or glial cells) could account more for the painDETECT scores than the sprouting of new nerves or anatomical lesions (such as those induced in entrapment neuropathies by chronic nerve compression or ischemia). For example, dysregulation of transcriptional repressors, such as neuron restrictive silencer factor, contributes to neuropathic pain through epigenetic mechanisms 37 and repression (by neuron restrictive silencer factor) of Nav1.8, leading to hypoesthesia and the repression of mu-opioid receptor genes, resulting in the loss of endorphins and morphine analgesia. 39…”
Section: Discussionmentioning
confidence: 99%
“…Initial data about neurodegenerative diseases were reported several years ago when reviews about the mechanisms of REST and its dependent therapies were first proposed. Details about these results can be found in previous and recent reviews [3,30]. Recent developments are illustrated here.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 79%
“…REST/NRSF is a transcriptional repressor that silences target genes through epigenetic remodelling and regulates neurogenesis, differentiation and the expression of specific neuronal genes in brain development. 20 REST was reported to regulate thousands of target genes. These genes encode neuronal receptors, ion channels, neuropeptides and synaptic proteins, and are closely related to synaptic plasticity and vesicle transport.…”
Section: Rest/nrsfmentioning
confidence: 99%